2002
DOI: 10.1523/jneurosci.22-16-06953.2002
|View full text |Cite
|
Sign up to set email alerts
|

Two Heteromeric Kv1 Potassium Channels Differentially Regulate Action Potential Firing

Abstract: Low-threshold voltage-gated potassium currents (I(LT)) activating close to resting membrane potentials play an important role in shaping action potential (AP) firing patterns. In the medial nucleus of the trapezoid body (MNTB), I(LT) ensures generation of single APs during each EPSP, so that the timing and pattern of AP firing is preserved on transmission across this relay synapse (calyx of Held). This temporal information is critical for computation of sound location using interaural timing and level differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
272
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(293 citation statements)
references
References 51 publications
20
272
1
Order By: Relevance
“…Kv1.1-and Kv1.2-specific toxins displayed comparable levels of current inhibition, and their effects were not additive, and so we propose that these subunits comprise a heteromer, rather than two subpopulations of homomeric channels. Kv1.1/Kv1.2 heteromeric channels have been identified elsewhere within the auditory pathway, including the MNTB where they ensure rapid adaptation (Dodson et al, 2002). The properties of auditory neurons in Kv1.1-null and Kv1.2-null mutants have been assessed, but due to the heteromeric nature of the channels, interpretation of the results can be problematic.…”
Section: Kv11/kv12 Heteromeric Channels Mediate Lva Currents In Matmentioning
confidence: 99%
“…Kv1.1-and Kv1.2-specific toxins displayed comparable levels of current inhibition, and their effects were not additive, and so we propose that these subunits comprise a heteromer, rather than two subpopulations of homomeric channels. Kv1.1/Kv1.2 heteromeric channels have been identified elsewhere within the auditory pathway, including the MNTB where they ensure rapid adaptation (Dodson et al, 2002). The properties of auditory neurons in Kv1.1-null and Kv1.2-null mutants have been assessed, but due to the heteromeric nature of the channels, interpretation of the results can be problematic.…”
Section: Kv11/kv12 Heteromeric Channels Mediate Lva Currents In Matmentioning
confidence: 99%
“…Further, the K v 1 family of channels are known to form heteromeric and homomeric complexes with differing properties (Ruppersberg et al, 1990;Hopkins et al, 1994), thus adding to the complexity of excitability available to spiral ganglion neurons. Hypothetically, however, a mechanism as simple as depolarization-induced K v 1 inactivation (Dodson et al, 2002) can have a profound effect on the transition to different accommodation classes that would essentially provide instantaneous, yet reversible, regulatory control. Conversely, neurotrophin exposure could activate intracellular signaling systems and engage gene transcription programs that would result in longer-lasting changes in ion channel composition.…”
Section: Regulatory Controls Of Accommodation Response Modementioning
confidence: 99%
“…The voltage sensitivity, kinetics, and dendrotoxin sensitivity of I K(LVA) in MSO principal cells in many respects resembles that of other brainstem auditory neurons concerned with maintaining the precise timing of excitatory inputs, such as bushy and octopus cells of the VCN, and principal cells of the MNTB (Manis and Marx, 1991;Rathouz and Trussell, 1998;Bal and Oertel, 2001;Dodson et al, 2002;Rothman and Manis, 2003). In situ hybridization and immunocytochemical analyses also reveal that the Kv1.1 subunit is prominently expressed in these brainstem auditory nuclei (Grigg et al, 2000;Dodson et al, 2002;Lu et al, 2004). In the present study, we observed an increase in the amount of I K(LVA) blocked by DTX-K between P14 and P21 (76 to 91% block), possibly reflecting an increase in the proportion of channels containing Kv1.1.…”
Section: Properties and Developmental Regulation Of I K(lva) In Mso Pmentioning
confidence: 99%
“…These developmental changes are mediated primarily by an increase in I K(LVA) . Although MNTB principal neurons also express I K(LVA) (Banks and Smith, 1992;Brew and Forsythe, 1995;Dodson et al, 2002), their intrinsic properties do not change after hearing onset. Thus, the developmental refinement of electrical properties is not a general feature of all time-coding neurons.…”
Section: Introductionmentioning
confidence: 99%